Emergence of galactic morphologies at cosmic dawn: input from numerical modelling. Issue 1 (15th February 2022) - Bi, Da; Shlosman, Isaac; Romano-Díaz, Emilio
ABSTRACT: We employ a series of high-resolution zoom-in cosmological simulations to analyse the emerging morphology of main galaxies in dark matter haloes at z ≳ 2. We choose haloes of similar masses, log M_vir/M_11.65± 0.05, at the target z f = 6, 4, and 2. The rationale for this choice allows us to analyse how the different growth rate in these haloes propagates down to galaxy scales, affecting their basic parameters. Halos were embedded in high/low overdensity regions, and two versions of a galactic wind feedback were employed. Our main results are: (1) Although our galaxies evolve in different epochs, their global parameters remain within narrow range. Their morphology, kinematics, and stellar populations differ substantially, yet all host sub-kpc stellar bars; (2) The star formation rates appear higher for larger z f ; (3) Bulges and stellar spheroids were separated by stellar kinematics, discy bulges were revealed using the Sersic method and photometry.The bulge-to-total mass ratios appear independent of the last merger time for all z f . The spheroid-to-total mas ratios lie within ∼0.5–0.8; (4) The synthetic redshifted, pixelized, and PSF-degraded JWST images allow detection of stellar discs at all z f . (5) Based on the kinematic decomposition, rotational support in discs depends on the feedback type, but increases with decreasing z f ; (6) Finally, the ALMA images detect discs at all z f, but spiral structure is detectable in z f = 2 galaxies. Moreover, galaxies follow the Tully–Fisher relation, being separated only by the galactic wind feedback.